None Questions

Question Number 2970 by Syaka last updated on 01/Dec/15

$$\underset{\mathrm{0}} {\overset{\frac{\pi}{\mathrm{2}}} {\int}}\underset{\mathrm{0}} {\overset{{z}} {\int}}\underset{\mathrm{0}} {\overset{{y}} {\int}}\:{sin}\:\left({x}\:+\:{y}\:+\:{z}\right)\:{dx}\:{dy}\:{dz}\:=\:...? \\$$

Answered by Yozzi last updated on 02/Dec/15

$$\int{sin}\left({x}+{b}\right){dx}\:{let}\:{u}={x}+{b}\Rightarrow{du}={dx} \\$$ $$\therefore\int{sinudu}=−{cosu}+{C}=−{cos}\left({x}+{b}\right)+{C} \\$$ $$\therefore\:\int_{\mathrm{0}} ^{{y}} {sin}\left({x}+{y}+{z}\right){dx}=−{cos}\left({x}+{y}+{z}\right)\mid_{\mathrm{0}} ^{{y}} \\$$ $$\int_{\mathrm{0}} ^{{y}} {sin}\left({x}+{y}+{z}\right){dx}={cos}\left({y}+{z}\right)−{cos}\left(\mathrm{2}{y}+{z}\right) \\$$ $$\therefore\int_{\mathrm{0}} ^{{z}} \int_{\mathrm{0}} ^{{y}} {sin}\left({x}+{y}+{z}\right){dxdy} \\$$ $$=\int_{\mathrm{0}} ^{{z}} {cos}\left({y}+{z}\right)−{cos}\left(\mathrm{2}{y}+{z}\right){dy} \\$$ $$={sin}\left({y}+{z}\right)−\frac{\mathrm{1}}{\mathrm{2}}{sin}\left(\mathrm{2}{y}+{z}\right)\mid_{\mathrm{0}} ^{{z}} \\$$ $$={sin}\mathrm{2}{z}−\mathrm{0}.\mathrm{5}{sin}\mathrm{3}{z}−\left({sinz}−\mathrm{0}.\mathrm{5}{sinz}\right) \\$$ $$={sin}\mathrm{2}{z}−\mathrm{0}.\mathrm{5}{sin}\mathrm{3}{z}−\mathrm{0}.\mathrm{5}{sinz} \\$$ $$\therefore\int_{\mathrm{0}} ^{\pi/\mathrm{2}} \int_{\mathrm{0}} ^{{z}} \int_{\mathrm{0}} ^{{y}} {sin}\left({x}+{y}+{z}\right){dxdydz} \\$$ $$=\int_{\mathrm{0}} ^{\pi/\mathrm{2}} {sin}\mathrm{2}{z}−\mathrm{0}.\mathrm{5}{sin}\mathrm{3}{z}−\mathrm{0}.\mathrm{5}{sinzdz} \\$$ $$=−\mathrm{0}.\mathrm{5}{cos}\mathrm{2}{z}+\frac{\mathrm{1}}{\mathrm{6}}{cos}\mathrm{3}{z}+\mathrm{0}.\mathrm{5}{cosz}\mid_{\mathrm{0}} ^{\pi/\mathrm{2}} \\$$ $$=−\mathrm{0}.\mathrm{5}\left(−\mathrm{1}\right)+\mathrm{0}+\mathrm{0}−\left(−\mathrm{0}.\mathrm{5}+\mathrm{0}.\mathrm{5}+\frac{\mathrm{1}}{\mathrm{6}}\right) \\$$ $$=\frac{\mathrm{1}}{\mathrm{2}}−\frac{\mathrm{1}}{\mathrm{6}} \\$$ $$=\frac{\mathrm{6}−\mathrm{2}}{\mathrm{12}} \\$$ $$=\frac{\mathrm{1}}{\mathrm{3}} \\$$ $$\\$$ $$\\$$

Commented byFilup last updated on 02/Dec/15

$$\left.{damn},\:{you}\:{beat}\:{me}!\:;\right) \\$$

Commented bySyaka last updated on 02/Dec/15

$${Thanks}\:{Sir},\:{I}\:{always}\:{learn}\:{from}\:{you}. \\$$

Answered by Filup last updated on 03/Dec/15

$$\underset{\mathrm{0}} {\overset{\pi/\mathrm{2}} {\int}}\underset{\mathrm{0}} {\overset{{z}} {\int}}\underset{\mathrm{0}} {\overset{{y}} {\int}}\:\mathrm{sin}\left({x}+{y}+{z}\right)\:{dx}\:{dy}\:{dz} \\$$ $$\\$$ $$=\underset{\mathrm{0}} {\overset{\pi/\mathrm{2}} {\int}}\underset{\mathrm{0}} {\overset{{z}} {\int}}\:−\left[\mathrm{cos}\left({x}+{y}+{z}\right)\right]_{{x}=\mathrm{0}} ^{{x}={y}} \:{dy}\:{dz} \\$$ $$=\underset{\mathrm{0}} {\overset{\pi/\mathrm{2}} {\int}}\underset{\mathrm{0}} {\overset{{z}} {\int}}\:\left(\mathrm{cos}\left({y}+{z}\right)−\mathrm{cos}\left(\mathrm{2}{y}+{z}\right)\right)\:{dy}\:{dz} \\$$ $$=\underset{\mathrm{0}} {\overset{\pi/\mathrm{2}} {\int}}\:\left[\mathrm{sin}\left({y}+{z}\right)−\frac{\mathrm{1}}{\mathrm{2}}\mathrm{sin}\left(\mathrm{2}{y}+{z}\right)\right]_{{y}=\mathrm{0}} ^{{y}={z}} \:{dz} \\$$ $$=\underset{\mathrm{0}} {\overset{\pi/\mathrm{2}} {\int}}\:\left(\mathrm{sin}\left(\mathrm{2}{z}\right)−\frac{\mathrm{1}}{\mathrm{2}}\mathrm{sin}\left(\mathrm{3}{z}\right)\right)−\left(\mathrm{sin}\left({z}\right)−\frac{\mathrm{1}}{\mathrm{2}}\mathrm{sin}\left({z}\right)\right)\:{dz} \\$$ $$=\underset{\mathrm{0}} {\overset{\pi/\mathrm{2}} {\int}}\:\left(\mathrm{sin}\left(\mathrm{2}{z}\right)−\frac{\mathrm{1}}{\mathrm{2}}\mathrm{sin}\left(\mathrm{3}{z}\right)−\frac{\mathrm{1}}{\mathrm{2}}\mathrm{sin}\left({z}\right)\right)\:{dz} \\$$ $$=\left[−\frac{\mathrm{1}}{\mathrm{2}}\mathrm{cos}\left(\mathrm{2}{z}\right)+\frac{\mathrm{1}}{\mathrm{6}}\mathrm{cos}\left(\mathrm{3}{z}\right)+\frac{\mathrm{1}}{\mathrm{2}}\mathrm{cos}\left({z}\right)\right]_{{z}=\mathrm{0}} ^{{z}=\pi/\mathrm{2}} \\$$ $$\\$$ $$=\left(−\frac{\mathrm{1}}{\mathrm{2}}\mathrm{cos}\left(\pi\right)+\frac{\mathrm{1}}{\mathrm{6}}\mathrm{cos}\left(\frac{\mathrm{3}\pi}{\mathrm{2}}\right)+\frac{\mathrm{1}}{\mathrm{2}}\mathrm{cos}\left(\frac{\pi}{\mathrm{2}}\right)\right) \\$$ $$−\left(−\frac{\mathrm{1}}{\mathrm{2}}\mathrm{cos}\left(\mathrm{0}\right)+\frac{\mathrm{1}}{\mathrm{6}}\mathrm{cos}\left(\mathrm{0}\right)+\frac{\mathrm{1}}{\mathrm{2}}\mathrm{cos}\left(\mathrm{0}\right)\right) \\$$ $$\\$$ $$\mathrm{cos}\left(\mathrm{0}\right)=\mathrm{1},\:\:\:\:\mathrm{cos}\left({n}\pi\right)=−\mathrm{1},\:\:\:\:\mathrm{cos}\left(\frac{{n}\pi}{\mathrm{2}}\right)=\mathrm{0},\:\:\:\:{n}\in\mathbb{Z} \\$$ $$=\left(\frac{\mathrm{1}}{\mathrm{2}}+\mathrm{0}+\mathrm{0}\right)−\left(−\frac{\mathrm{1}}{\mathrm{2}}+\frac{\mathrm{1}}{\mathrm{6}}+\frac{\mathrm{1}}{\mathrm{2}}\right) \\$$ $$=\frac{\mathrm{1}}{\mathrm{2}}+\frac{\mathrm{1}}{\mathrm{2}}−\frac{\mathrm{2}}{\mathrm{3}} \\$$ $$=\mathrm{1}−\frac{\mathrm{2}}{\mathrm{3}} \\$$ $$=\frac{\mathrm{1}}{\mathrm{3}} \\$$ $$\\$$ $$\therefore\underset{\mathrm{0}} {\overset{\pi/\mathrm{2}} {\int}}\underset{\mathrm{0}} {\overset{{z}} {\int}}\underset{\mathrm{0}} {\overset{{y}} {\int}}\:\mathrm{sin}\left({x}+{y}+{z}\right)\:{dx}\:{dy}\:{dz}\:=\:\frac{\mathrm{1}}{\mathrm{3}} \\$$

Commented bySyaka last updated on 02/Dec/15

$${Thanks}\:{for}\:{Solution}\:{Sir},\:{I}\:{like}\:{that} \\$$